Design, Synthesis, and Pharmacology of New Triazole-Containing Quinolinones as CNS Active Agents - Wennan Zhao; Mingxia Song; Yi Hua; Yangnv Zhu; Wenli Liu; Qishan Xia; Xianqing Deng; Yushan Huang (Molecules, 2023)
Epilepsy and major depressive disorder are the two of the most common central nervous system (CNS) diseases. Clinicians and patients call for new antidepressants, antiseizure medicines, and in particular drugs for depression and epilepsy comorbidities. In this work, a dozen new triazole-quinolinones were designed, synthesized, and investigated as CNS active agents. All compounds reduced the immobility time significantly during the forced swim test (FST) in mice at the dosage of 50 mg/kg. Compounds 3f–3j gave superior performance over fluoxetine in the FST with more reductions of the immobility time. Compound 3g also reduced immobility time significantly in a tail suspension test (TST) at the dosage of 50 mg/kg, though its anti-immobility activity was inferior to that of fluoxetine. An open field test was carried out and it eliminated the false-positive possibility of 3g in the FST and TST, which complementarily supported the antidepressant activity of 3g. We also found that almost all compounds except 3k exhibited antiseizure activity in the maximal electroshock seizure (MES) model at 100 or 300 mg/kg. Compounds 3c, 3f, and 3g displayed the ED50 of 63.4, 78.9, and 84.9 mg/kg, and TD50 of 264.1, 253.5, and 439.9 mg/kg, respectively. ELISA assays proved that the mechanism for the antiseizure and antidepressant activities of compound 3g was via affecting the concentration of GABA in mice brain. The molecular docking study showed a good interaction between 3g and the amino acid residue of the GABAA receptor. Excellent drug-like properties and pharmacokinetic properties of compound 3a–l were also predicted by Discovery Studio. These findings provided a new skeleton to develop agents for the treatment of epilepsy and depression comorbidities.